Characterization of Bubble Entrainment, Interfacial Roughness and the Sliding Bubble Mechanism in Horizontal Annular Flow - Rodriguez, Daniel J. (University of Wisconsin-Madison, 2004)
Flow boiling inside pipes is a widely implemented means of heat transfer in many branches of industry and energy generation. However, the nature and relative importance of the un- derlying mechanisms linked to this type of process are still a matter of controversy. This study addresses three particular aspects of the mechanistic approach for the explanation of flow boiling heat transfer. The flow mechanics observed in horizontal two-phase adiabatic air/water flow are studied in an effort to explain flow boiling. Specifically, entrained bubble behavior related to the sliding bubble heat transfer mechanism and pressure drop in the an- nular flow regime are studied using three optical techniques. Backlit bubble contour imaging is used to obtain estimates of the size distribution and entrained bubble concentration within the thin liquid film in annular flow. Planar Laser Induced Fluorescence (PLIF) is used for qualitatively documenting the bubble entrainment mechanism associated with disturbance waves in annular flow. The PLIF technique also proves useful in directly measuring the film thickness and interfacial roughness of the flow. A more integral view of the pressure drop mechanisms that exist in annular flow is obtained as a result of an automated analysis of the roughness data. A CFD simulation of the sliding bubble mechanism is used to predict the effect of bubble diameter and outer flow conditions on the modulation of turbulence. The results from the simulation are used in constructing an understanding of the cooling effect of individual sliding bubbles associated with enhanced turbulent mixing. Finally, a cross-cut micro-scale particle image velocimetry (PIV) system with micron scale spatial resolution is proposed for studying the dynamic behavior of entrained bubbles and the liquid flow around them. The estimation of the cumulative effect of a given concentration, size distribution and radial location of entrained bubbles, coupled to the knowledge of the flow parameters that produce those entrainment characteristics, can help elucidate the physics represented by empirical quantities in current saturated flow boiling heat transfer models.
Under the supervision of Assistant Professor Timothy Shedd; 232pp.
Keywords: Thesis (Ph.D.)--University of Wisconsin--Madison, 2004.; Dissertations Academic Mechanical Engineering.; University of Wisconsin--Madison. College of Engineering.